Organology of Dreams and Archi-Cinema ( - Bernard, Stiegler (The Nordic Journal of Aesthetics, 2016)
Stiegler argued in Cinematic Time and the Question of Malaise (the third volume of Technics and Time) that we must refer to archi-cinema just as Derrida spoke of archi-writing. In this article he proposes that in principle the dream is the primordial form of this archi-cinema. The archi-cinema of consciousness, of which dreams would be the matrix as archi-cinema of the unconscious, is the projection resulting from the play between what Husserl called, on the one hand, primary and secondary retentions, and what Stiegler, on the other hand, calls tertiary retentions, which are the hypomnesic traces (that is, the mnemo-technical traces) of conscious and unconscious life. There is archi-cinema to the extent that for any noetic act – for example, in an act of perception – consciousness projects its object. This projection is a montage, of which tertiary (hypomnesic) retentions form the fabric, as well as constituting both the supports and the cutting room. This indicates that archi-cinema has a history, a history conditioned by the history of tertiary retentions. It also means that there is an organology of dreams.